Spiritualitas Kairologi Natal: Kritik terhadap Perayaan Natal di Gereja HKBP yang sudah Mentradisi namun Bertolak Belakang dengan Kalender Gerejawi - Nixcon Simanungkalit (STT HKBP Pematangsiantar, 2024)
The article explores the intricacies of the decade-long debate surrounding the celebration of Christmas in the HKBP Church. Internal tensions have grown due to differing opinions on the date of Christmas observance. Despite attempts to restore traditions in line with the liturgical calendar, internal conflicts and external pressures remain formidable obstacles. The author underscores the importance of understanding two dimensions of time, namely chronos and kairos, by referencing Joas Adiprasetya's thoughts. Providing intriguing insights through a profound understanding of the historical shifts in Christmas traditions in the HKBP Church, influenced by historical and political events, this article highlights significant hurdles from both internal and external factors. It explores how an inaccurate understanding of the liturgical calendar can adversely impact the liturgical meaning of Christmas celebration in the HKBP Church.